A Proposal for Extending the Theory of the Firm - Cooper, W. W. (Quarterly Journal of Economics, 1951)
I. Introduction, 87. — II. The business firm as organization, 89. — III. Control and costs, 91. — IV. Standard costs, 94. — V. Agent behavior, 98. — VI. Multiple commodity production and multiple agents — horizontal case, 103. — VII. Multiple agents — vertical case, 105. — VIII. Conclusion, 109.